Corpus-based english for sport sciences: a systematic review of specialised vocabulary, terminology, and pedagogical applications (2015–2025) - Kristian Burhan; Ifdil Ifdil; Rudyanto Rudyanto (Lentera Negeri, 2026)
English has become the dominant language of communication in sport sciences, yet many students continue to experience difficulties in acquiring specialised vocabulary, technical terminology, and discipline-specific discourse required for academic and professional contexts. Although corpus linguistics offers a robust evidence-based approach for identifying authentic language patterns, its pedagogical application in sport sciences remains fragmented. This systematic literature review synthesises empirical evidence on corpus-based English research relevant to sport sciences education. The review followed the PRISMA 2020 guidelines and searched the Scopus database because of its comprehensive coverage of peer-reviewed interdisciplinary literature in linguistics, education, and sport sciences. A structured Boolean search identified 403 records, of which 18 studies (2015–2025) met the predefined eligibility criteria after duplicate removal, title and abstract screening, and full-text assessment based on the PICOS framework. Two independent reviewers conducted the screening and data extraction process, with disagreements resolved through discussion. Methodological quality was evaluated using the FICO framework, and evidence was synthesised through the thematic synthesis approach proposed by Thomas and Harden (2008). Four overarching themes emerged: (1) specialised vocabulary development and word-list construction, (2) sport terminology and cross-linguistic variation, (3) spoken and instructional discourse in sport contexts, and (4) corpus-informed pedagogical applications. The findings indicate that technical vocabulary and multiword expressions constitute a substantial proportion of sport science discourse, while inconsistencies in terminology across languages continue to challenge instructional standardisation. Nevertheless, most existing studies remain descriptive, with relatively few evaluating instructional effectiveness or learning outcomes. This review provides a comprehensive synthesis of corpus-based evidence and highlights the need for discipline-specific teaching materials, corpus-informed curricula, and intervention studies evaluating pedagogical effectiveness. The findings offer practical guidance for English for Specific Purposes (ESP) curriculum development and establish directions for future corpus-based research in sport sciences education.